2014
DOI: 10.2991/jrnal.2014.1.3.15
|View full text |Cite
|
Sign up to set email alerts
|

Novel Opt-coupling Transistor by LED and PD and its Application

Abstract: This paper proposes a novel transistor-like device by the optical coupling of LED (Light Emitting Diode) and Photodiode. The device that we call "OCT: Optical Coupling Transistor" shows an amplification function if the Photodiode current by photo electromotive force is feed backed into the LED, in the same way as the case of common emitter circuit of the conventional Bipolar Junction Transistor. In this paper, we present the amplification principle and its applications by OCT such as audio amplifier and operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In order for the image processing to have such arrangement capability, we would like to introduce some related processing methods of Signal Processing in Kansei Engineering, Time Series Analysis, and Advection Diffusion in Fluid Dynamics. [11][12][13][14][15]…”
Section: Resultsmentioning
confidence: 99%
“…In order for the image processing to have such arrangement capability, we would like to introduce some related processing methods of Signal Processing in Kansei Engineering, Time Series Analysis, and Advection Diffusion in Fluid Dynamics. [11][12][13][14][15]…”
Section: Resultsmentioning
confidence: 99%
“…Later, an audio amplifier prototype using PTT positive feedback circuit with optical coupling between highbrightness LED and PD was developed, and it was reported that the PTT even exhibited functions similar to those of a thyristor ( [3], [4], [5], [6], [7], [8]). Also, while referencing the conventional studies on BJT ( [9], [10], [11], [12]), authors have analyzed the current amplification function of the PTT based on experimental results ( [13], [14]).…”
Section: Introductionmentioning
confidence: 99%
“…After that, it has been reported that, using the PTT that consists of high-brightness LED and PD ( [3], [4], [5]). audio amplifier can be developed and that the PTT expresses not only an amplification function but also a switching function similar to a thyristor ( [6], [7], [8]).…”
Section: Introductionmentioning
confidence: 99%